The Effectiveness of Modified Children’s Songs as a Teaching Tool in Indonesian Language Instruction for Expanding the Vocabulary of Elementary School Students - Febi Hauliya; Maria Goreti Rini Kristiantari; Anak Agung Ayu Dewi Sutyaningsih (Universitas Pendidikan Ganesha, 2026)
Indonesian language learning in elementary schools still faces challenges in students’ mastery of new vocabulary due to the limited use of engaging learning media that suit students’ characteristics. This study aimed to develop and examine the effectiveness of modified children’s songs as learning media to improve elementary school students’ mastery of new vocabulary. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The subjects of this study were 32 third grade elementary school students. Data were collected through observations, interviews, questionnaires, and tests using expert validation sheets, teacher and student response questionnaires, as well as pretest and posttest instruments. Data analysis was conducted using descriptive quantitative analysis and a t-test. The findings showed that the modified children’s song media achieved a very good category, with material expert validation reaching 95.83% and media expert validation reaching 92.50%. The t-test results indicated that the use of the media significantly improved students’ mastery of new vocabulary. The study concludes that modified children’s song media are feasible and effective for use in Indonesian language learning to improve elementary school students’ vocabulary mastery. The implication of this study shows that children’s song-based media can serve as an innovative alternative for creating more creative, contextual, and student-centered Indonesian language learning.